2014
DOI: 10.1364/ol.39.006308
|View full text |Cite
|
Sign up to set email alerts
|

Timing and phase jitter suppression in coherent soliton transmission

Abstract: We have revisited soliton transmission in the new context of coherent optical detection optimizing and comparing digital backward propagation and in-line optical filtering as a means to suppress soliton timing and phase jitter. We find that in-line optical filtering allows one to improve the reach of the soliton system by up to the factor of 2. Our results show that nonlinear propagation can lead to performance beyond the nonlinear Shannon limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… For long distance systems with large spectra (short pulses in the soliton context) acoustooptic and Raman effects should not be neglected. Whilst explicit research into soliton transmission systems is now rare, recent calculations have shown the benefit of multi-level phase modulated solitons [91,92] and continued interest in dispersion management [93,94] and control [95] of optical solitons. The broader lessons of soliton transmission systems are currently being revised through the generalized concept of the nonlinear Fourier transform [96], and calculations of potential performance limits are now under way [97].…”
Section: Soliton Transmission Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“… For long distance systems with large spectra (short pulses in the soliton context) acoustooptic and Raman effects should not be neglected. Whilst explicit research into soliton transmission systems is now rare, recent calculations have shown the benefit of multi-level phase modulated solitons [91,92] and continued interest in dispersion management [93,94] and control [95] of optical solitons. The broader lessons of soliton transmission systems are currently being revised through the generalized concept of the nonlinear Fourier transform [96], and calculations of potential performance limits are now under way [97].…”
Section: Soliton Transmission Systemsmentioning
confidence: 99%
“…In the case of soliton transmission the performance is then primarily dominated by the interaction of the signal with noise through Gordon Haus jitter [82]. However, this approach is somewhat restrictive in the use of pulse shapes, and until recently multiamplitude level solitons had not been considered [197]. In principle, the inter signal nonlinearity discussed (first term of equation 25) above is deterministic and thus can be fully compensated as was first described using a concept of inverse nonlinear transmission at the receiver [198] even in the case of solitons.…”
Section: Performance Limits With Nonlinearity Compensationmentioning
confidence: 99%
“…Many detailed models for η C exist [6][7][8][9][10][11][12], showing a dependence on the receiver sampling rate and step size [14] (if applicable), the effective bandwidth and parasitic effects such as PMD [6,7]. Whilst digital back propagation (DBP) is effective [2][3][4][5][6][7] it's perceived complexity makes the use of signal conjugates attractive, either by sending an orthogonal conjugated copy (OCC) [13] of the signal along the same transmission line, or by coding the conjugate with the signals (CCC) [14][15]. In the latter case, M C =1 in Eqn.…”
Section: Noise Sources In Long Haul Transmission Systemsmentioning
confidence: 99%
“…However, the compensation of nonlinear effects which arise from stochastic effects, such as polarisation mode dispersion (PMD) and noise, presents significant challenges. Several forms of nonlinear interaction with noise have been investigated, such as nonlinear phase noise which manifests strongly in dispersion managed systems [3], or Gordon-Mollenauer noise which is dominant for amplitude stabilised systems such as solitons [4]. However, for long haul, dispersion unmanaged, high spectral efficiency systems the dominant stochastic nonlinearity is parametric noise amplification [5][6][7], which is related to modulation instability and depends quadratically on the signal intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing and reducing impairments for transmission of fundamental solitons has been a central theme for telecommunication researchers and the wider nonlinear optics community. In long-haul soliton transmissions, periodic signal amplification with spontaneous emission noise results in soliton jitters known as Gordon-Haus effect [3][4][5], which is a long-standing problem in soliton transmissions. Additionally, in soliton systems where soliton pulse trains are generated and detected one pulse after the other, a linear superposition of two soliton pulses are in general not a solitonic solution to the Nonlinear Schrodinger Equation (NLSE) and hence neighboring pulses will interact with each other along propagation.…”
Section: Introductionmentioning
confidence: 99%